GAMBARAN PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) LANSIA PADA TATANAN RUMAH TANGGA - Ronasari Mahaji Putri (Dian Nuswantoro Semarang, 2019)
Elderly is an age group that has experienced a decline from many aspects, namely physical, psychological and social. With this limitation, it will greatly affect the ability / independence in implementing PHBS. Healthy behavior supporting successful aging in the elderly The aim of the study is to describe the application of Clean and Healthy Life Behavior (PHBS) to the elderly in the household setting. This research is a descriptive research. The study population was all elderly in RT 03 RW 06 Tlogomas Malang with 41 people, samples were taken using total sampling technique. The instrument used was a PHBS questionnaire containing 10 indicators of 20 questions. Data collection was carried out through questionnaires accompanied by mentoring the elderly in answering the questionnaire questions. Data analysis was carried out with the help of SPSS version 17 using the univariate test. The results of the study revealed that most of the elderly had the application of PHBS in the Good category. However, indicators of elderly PHBS namely eradicating mosquito larvae, exercising regularly, and smoking in the house still show a bad category.